Anti-money laundering and its companions : a paradigm for the future - Carmichael, Trevor (1999)
Examines some salient features of money laundering and commercial crime. Explores some of the Caribbean legislative and regulatory responses. Focuses on some of the special features of the low tax and no tax jurisdictions in relation to money laundering and financial crimes. Explores the future challenges which the new technologies will bring to judges, regulators and professionals concerned with the dangers of financial crimes.